Opposite changes in APP processing and human Aβ levels in rats carrying either a protective or a pathogenic APP mutation - Tambini, Marc D (eLife, 2020)
Cleavage of APP by BACE1/β-secretase initiates the amyloidogenic cascade leading to Amyloid-β (Aβ) production. α-Secretase initiates the non-amyloidogenic pathway preventing Aβ production. Several APP mutations cause familial Alzheimer’s disease (AD), while the Icelandic APP mutation near the BACE1-cleavage site protects from sporadic dementia, emphasizing APP’s role in dementia pathogenesis. To study APP protective/pathogenic mechanisms, we generated knock-in rats carrying either the protective (App(p)) or the pathogenic Swedish mutation (App(s)), also located near the BACE1-cleavage site. α-Cleavage is favored over β-processing in App(p) rats. Consequently, non-amyloidogenic and amyloidogenic APP metabolites are increased and decreased, respectively. The reverse APP processing shift occurs in App(s) rats. These opposite effects on APP β/α-processing suggest that protection from and pathogenesis of dementia depend upon combinatorial and opposite alterations in APP metabolism rather than simply on Aβ levels. The Icelandic mutation also protects from aging-dependent cognitive decline, suggesting that similar mechanisms underlie physiological cognitive aging.